2018
DOI: 10.3390/rs10111761
|View full text |Cite|
|
Sign up to set email alerts
|

Assessing Pasture Degradation in the Brazilian Cerrado Based on the Analysis of MODIS NDVI Time-Series

Abstract: Around 55% of all Brazilian cattle production is located in the Cerrado biome, which also contains the largest pasture area in Brazil. Previous studies indicated that about 60% of these pastures were degraded by 2010. However, up-to-date and more precise estimates are necessary to access the extent and degree of degradation of the Cerrado pastures, since these areas constitute strategic land reserves for both livestock intensification and soybean expansion. Therefore, in this study, we estimated the area of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 23 publications
2
42
0
7
Order By: Relevance
“…The effects of pasture degradation detected in this study region may influence a reduction in livestock areas, as pointed out in a recent study, despite a relative increase of 17% in pasture areas in the Brazilian territory during the 21 st century [59]. A prior study also suggested that social aspects, such as low levels of human development presented by municipalities, may influence the environmental and grassland degradation associated with decreased rainfall and the adoption of improper soil conservation practices [60].…”
Section: Discussionsupporting
confidence: 53%
“…The effects of pasture degradation detected in this study region may influence a reduction in livestock areas, as pointed out in a recent study, despite a relative increase of 17% in pasture areas in the Brazilian territory during the 21 st century [59]. A prior study also suggested that social aspects, such as low levels of human development presented by municipalities, may influence the environmental and grassland degradation associated with decreased rainfall and the adoption of improper soil conservation practices [60].…”
Section: Discussionsupporting
confidence: 53%
“…However, agriculture is already the major user of water in the world, accounting for 30-40% of freshwater withdrawals in the OECD countries and 70% globally. It is also a major contributor to the global emissions of greenhouse gases [11].…”
Section: Introductionmentioning
confidence: 99%
“…Rather than a completely new method, this is a strategy that tries to reduce as much as possible the negative impacts caused by invalid data. S-G is selected as the basic filtering method since it is still widely reported in the recent literature [30], [38]- [41]. Its popularity is mainly attributed to its effectiveness in removing noise and ability to preserve the shape of peaks in the signal waveform.…”
Section: Introductionmentioning
confidence: 99%